2019
DOI: 10.2147/ott.s184560
|View full text |Cite
|
Sign up to set email alerts
|

<p>High expression of NUCB2 promotes papillary thyroid cancer cells proliferation and invasion</p>

Abstract: Background NUCB2, a novel multifunctional protein containing several functional domains, was newly found to play important roles in many cancers, but its role in papillary thyroid cancer (PTC) is not well investigated. Therefore, our study was performed to explore the functions of NUCB2 in PTC. Methods NUCB2 protein level was analyzed by immunohistochemistry. Data analyses were made by performing chi-squared test. Quantitative reverse-transcription PCR, Western blot, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The expression levels of MMP-2 and MMP-9 in bladder cancer cells transfected with Nucb2 shRNA was lowered, indicating that Nucb2 may affect cancer migration and invasion through the MMP-2 and MMP-9 signaling pathways [ 26 ]. Analogous correlation was also recently found in papillary thyroid tumor cells [ 20 ], as well as previously for breast [ 13 ], renal [ 21 ], and colon [ 19 ] cancer cells. Similarly, in endometrial carcinoma cells [ 14 ], Nucb2 and its derivative nesfatin-1 significantly induced cell proliferation and migration.…”
Section: Nucb2 Involvement In Cancer Progressionsupporting
confidence: 87%
See 2 more Smart Citations
“…The expression levels of MMP-2 and MMP-9 in bladder cancer cells transfected with Nucb2 shRNA was lowered, indicating that Nucb2 may affect cancer migration and invasion through the MMP-2 and MMP-9 signaling pathways [ 26 ]. Analogous correlation was also recently found in papillary thyroid tumor cells [ 20 ], as well as previously for breast [ 13 ], renal [ 21 ], and colon [ 19 ] cancer cells. Similarly, in endometrial carcinoma cells [ 14 ], Nucb2 and its derivative nesfatin-1 significantly induced cell proliferation and migration.…”
Section: Nucb2 Involvement In Cancer Progressionsupporting
confidence: 87%
“…Despite the fact that its broad physiological function has been extensively investigated, there is also growing evidence that Nucb2 may play an important role in the multistep processes of tumorigenesis. A high expression of Nucb2, in comparison to adjacent non-cancerous cells, was found in breast [ 13 ], prostate [ 12 ], colon [ 19 ], endometrial [ 14 ], papillary thyroid [ 20 ], and renal cell carcinomas [ 21 ]. The immunoreactivity of Nucb2 was mainly detected in the cytoplasm of cancer cells [ 13 , 22 , 23 ].…”
Section: Nucb2 Involvement In Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…No relationship was found between NUCB2/NESF-1 and age, gender, or lymph node metastasis. [ 53 ]. Bearing in mind the above, it was speculated that NUCB2/NESF-1 could be a tumor promoter in papillary thyroid cancer.…”
Section: Nucb2—a Predictive/prognostic Biomarker In Cancers?mentioning
confidence: 99%
“…As a result, there is a need to identify new proliferation-related molecules in cancers. In vitro studies showed that NUCB2/NESF-1 knockdown with siRNA or shRNA in breast cancer (MCF-7, SKBR-3), bladder cancer (T24, 5637), glioblastoma (U251, U87), endometrial cancer (Ishikawa and Sawano), and thyroid cancer (TPC-I, KI) cell lines resulted in the inhibition of cell proliferation [ 41 , 47 , 50 , 53 , 58 ]. Moreover, proliferation-related proteins (Ki-67 and PCNA) were decreased in NUCB2/NESF-1 shRNA-transfected thyroid cancer cells compared to the control.…”
Section: Nucb2 In Cancer Proliferation Apoptosis Migration and Invasionmentioning
confidence: 99%